Alzheimer's disease: differences in technetium-99m HMPAO SPECT scan findings between early onset and late onset dementia. Issue 6 (1st June 2003) - Kemp, P M; Holmes, C; Hoffmann, S M A; Bolt, L; Holmes, R; Rowden, J; Fleming, J S
Abstract : Objective: To compare the HMPAO SPECT cerebral perfusion patterns in early and late onset Alzheimer's disease. Methods: Twenty patients with early onset disease (<65 years) and 44 patients with late onset disease (>65 years) were studied. All patients fulfilled NINCDS-ADRDA clinical criteria and had details of disease severity and length of history at the time of imaging. Technetium-99m HMPAO SPECT brain scans were acquired on a multi-detector gammacamera and analysed visually and with statistical parametric mapping (SPM99). Results: Patients with early onset disease had significantly greater posterior cortical association area involvement whereas those with late onset disease had significantly greater medial temporal hypoperfusion. These findings were unchanged after controlling for disease severity and length of illness. Discussion: These functional imaging findings of the differences between early and late onset Alzheimer's disease are supported by published findings that include histopathological and clinical evidence; namely late onset patients tend to present with the characteristic involvement of the medial temporal lobes producing marked memory loss whereas early onset patients present with predominant posterior cortical association area involvement. These age related findings should be borne in mind when clinically diagnosing, and interpreting functional brain imaging studies in, patients with suspected Alzheimer's disease.